Strengthening spice coffee SMEs based on digital marketing for sustainable business improvement - Andry Herawati; Sarwani Sarwani; Liling Listyawati; Sri Kamariyah; Didik Sugeng Widiarto (University of Merdeka Malang, 2023)
Digital marketing is a marketing strategy aimed at providing information to the community at large in an effective and efficient manner without being limited by space and time. This community partnership program aims to increase the understanding of the concept of digital marketing for spice coffee SMEs in Pertakina, Nglegok District, Blitar Regency as partners, by providing education, training, and mentoring. The results achieved increased partners' motivation and engagement to use digital marketing in spice coffee marketing, partners already have product logos and have created separate social media accounts for individuals and businesses. Partners can maintain their social media accounts by regularly uploading content about their spice coffee products to social media such as WhatsApp Group, Facebook, Instagram, and Youtube. The results of the evaluation with in-depth interviews show that there has been a development in the number of followers on social networks becoming more than before. This shows that there is life on social media, as evidenced by regular content uploads, catching viewers' attention and attracting consumer interest to follow spice coffee's social media.